From TikTok to Hard Fun: Progressive Engagement in Computational Thinking through Game Design (Constructionism Conference Proceedings, 2025)
This paper examines how constructionist learning principles can be maintained in an era of shortened attention spans and passive content consumption. While TikTok‘s own research shows that 50 % of users find videos over 60 seconds stressful, we demonstrate that meaningful creative engagement remains possible through carefully designed learning progressions. Using data from STEAM Discovery Fairs, we analyze how students across different grade levels and genders engage with RULER.game, a Computational Thinking Tool enabling rapid creation of programmable video game characters. Our findings reveal that while overall engagement levels were high, boys and girls derived enjoyment from different aspects – girls primarily from design elements and boys from programming components. The study demonstrates that by providing appropriate scaffolding and tools, students can quickly transition from passive consumers to active creators, even within perceived modern attention constraints. These results suggest that constructionist principles remain viable when learning designs thoughtfully balance cognitive and affective challenges while accounting for gender-specific preferences in creative computing activities.